PENGARUH HARGA PRODUK DAN PROMOSI TERHADAP VOLUME PENJUALAN BATIK SEMARANG 16 - Irene Nathalia Setiawan; Bambang Heriawan; Rusdiana Permanasari; Willyanto Kartiko Kusumo (ITB AAS Indonesia Surakarta, 2025)
The government should invest in all parts of the economy, but especially in the more nimble service and manufacturing sectors (fashion). Competition among businesses has heated up as the batik sector has expanded rapidly throughout the world. Many brands provide almost similar items, adding fuel to the fire. The younger generation, or millennials, in particular are getting more used to the concept of internet users as a result of the proliferation of various forms of digital communication. Internet marketing, especially the use of social media, has the potential to greatly boost revenue. Customers may more easily get the information they need without having to meet in person thanks to this. The development and sustainability of a company's goods are greatly affected by changes in sales volume. A product's potential for growth and market dominance is directly proportional to the company's sales figures, and vice versa.